2014
DOI: 10.1177/0898264314531618
|View full text |Cite
|
Sign up to set email alerts
|

Waist Circumference and Health-Related Quality of Life by Sex in the Korean Elderly

Abstract: Extreme obesity worsens mobility, and comorbidity in combination with obesity worsens HRQL in elderly women. Monitoring and controlling comorbidity and maintaining adequate WC decreases the risks of lowered HRQL in Korean elderly women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…VAI is highly associated with cardiovascular complications and insulin resistance [ 10 ], while body mass index (BMI) is incorrectly considered as a reasonable predictor for body fat percentage regardless of gender because of BMI is not always linked with cardiovascular mortalities [ 11 ]. Moreover, waist circumference (WC) has been regarded as an applicable index in the evaluation of adipose tissue distribution that is highly linked to visceral and abdominal obesity, but cannot distinguish between subcutaneous and visceral adipose tissue in the abdominal area [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…VAI is highly associated with cardiovascular complications and insulin resistance [ 10 ], while body mass index (BMI) is incorrectly considered as a reasonable predictor for body fat percentage regardless of gender because of BMI is not always linked with cardiovascular mortalities [ 11 ]. Moreover, waist circumference (WC) has been regarded as an applicable index in the evaluation of adipose tissue distribution that is highly linked to visceral and abdominal obesity, but cannot distinguish between subcutaneous and visceral adipose tissue in the abdominal area [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than half had detectable viral loads (54.0%), and were under HAART (58.0%). The mean duration (in months) since HAART initiation was 7.8 months (± 4.5; range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and six patients (11.8%) were on a single tablet regimen. HIV diagnosis took place in 2015 for most patients (68.6%).…”
Section: Study Sample Characteristics: Sociodemographic and Clinical mentioning
confidence: 99%
“…It is important to understand the impact nutritional status has on these patients' physical and mental health (3), since they are known to predict QoL. In the general population, lower anthropometric measurements are not only associated with a lower QoL, but being overweight or obese and having a high waist circumference have also been associated to morbidity and an impaired QoL (8).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in New Zealand with community elders found that obese individuals were 41% more likely of being at risk of using four or more medications and 30% more likely of being at risk of experiencing pain or discomfort, which negatively affected QoL 34 . Another study conducted in Korea concluded that the presence of comorbidities in overweight elderly patients negatively changed QoL 35 . The association between overweight and higher QoL scores in the social relationships realm diverges from the assumption that obesity can affect social, family and work relationships 36 , aspects evaluated in this realm 20 .…”
Section: Discussionmentioning
confidence: 99%